Optimizing the Use of Village Funds in Efforts to Develop Pethung Park Tourism in Belik Trawas Village, Mojokerto - Bayu Adji Pangestu; Zainal Fatah; Krisna Adhi Prahmana (International Journal of Social Science and Humanity, 2025)
This study aims to analyze the optimization of the use of Village Funds in efforts to develop Pethung Park tourism in Belik Village, Trawas District, Mojokerto Regency, using the New Public Governance (NPG) theoretical approach from Osborne and Gabler. NPG theory emphasizes the importance of collaboration, participation, networking, decentralization, as well as transparency and accountability in public governance. This study uses a qualitative descriptive method by collecting data through interviews, observations, and documentation involving the village government, BUMDes, Pokdarwis, and the local community. The results of the study show that the Belik Village government has succeeded in making optimal use of the Village Fund as an instrument of local economic development and a means of community empowerment. The Village Fund is directed to tourism infrastructure development, human resource training, and digital-based tourism promotion. Collaboration between village governments, communities, and the private sector through BUMDes and Pokdarwis is able to create participatory and sustainable development governance. The real impact can be seen from the increase in the number of tourist visits, the growth of MSMEs, and the increase in the village's original income. This study concludes that NPG-based governance practices in Belik Village have resulted in development effectiveness and strengthened village economic independence. The results of this study can be a model for other villages in implementing the management of Village Funds for the tourism sector based on collaboration and community participation towards sustainable village development.